Drug eruption caused by imatinib in a patient with gastrointestinal stromal tumour – case report - Baran, Anna; Flisiak, Iwona; Myśliwiec, Hanna; Chodynicka, Bożena (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Gastrointestinal stromal tumour (GIST) is a rare mesenchymal tumour of the gastrointestinal tract and mesentery. Standard treatment is surgical resection. First-line therapy of unresectable or metastatic GIST is imatinib mesylate – a tyrosine kinase inhibitor. Objective . The aim of this paper is to present a patient with GIST in whom treatment with imatinib caused dermatitis as an adverse effect and a change of therapy was necessary. Case report . We present a case of a 57-year-old woman with nonoperative GIST diagnosed 2 years ago in whom, after 3 months of treatment with imatinib, papulo-erythematous, pruritic eruption on the trunk, lower and upper extremities and face occurred. The histopathological picture corresponded with lichenoid reaction caused by the drug. Despite lowering the dose of imatinib, new infiltrated lesions with a tendency to disintegration were observed. Due to systemic (intravenous pulses of corticosteroids, antihistaminics) and topical treatment (corticosteroid ointments) and the change of imatinib for a second-line drug, sunitinib, improvement of skin lesions was observed. Conclusions . Therapy with imatinib is generally well tolerated, but dermatitis can appear in 30% of patients taking this drug. In the presented case with unresectable GIST therapy with imatinib caused skin complications.